TRANSFORMATION OF POLITICAL MODES IN THE CONDITIONS OF GEOPOLITICAL TURBULENCE - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article analyzes the key factors, trends and prospects for the transformation of political regimes in the context of transition to a polycentric world order. Geopolitical uncertainties are causing significant apprehension among elite and scientists at the beginning new era. This is due to some change in the hegemony of the world powers. The nature of hegemony, changing world order received special attention in the twentieth century and remains  in the focus of researches  to this day I Wallerstein stressed that the hegemonic states   must be powerful to receive the benefits of its status. «Unipolar order» in world politics has turned out to be dysfunctional in terms of ensuring global prosperity and security, promoting democratic practices, and strengthening world order and stability across  all regions. Destabilization of the entire world order is due to aggravating internal political divisions and confrontations in the USA and in the countries of the European Union.Processes of reforming new  geopolitical coalitions have provided geopolitical turbulence. Turbulent world of international relations and politics is characterized  by two overarching trends: (1) the supersession of geopolitics by geoeconomics; (2) mutations of the international security which is increasingly shifting from the interstate level to security threats the growing importance and intensity of conflicts between different value systems and ideologies, in particular between integrationist (such as democracy and human rights) and particularistic ideologies (such as  nationalism or religious fundamentalism). Confrontation of the processes of Westernization and Easternization  means the weakening of influence of Western countries and strengthening of Eastern. According to some forecasts, economic and technological revolutions will change the economies and social structures of societies; social and democratic revolutions will exert pressure on different levels of government; the geopolitical revolution will create a multipolar world. In the conditions of geopolitical turbulence main courses of power are eroded and predict the trajectories of the transformation of political regimes in the coming decades, especially in the face of strengthening Asia and Latin America, is too complicated.